State of the Art Computational Ternary Logic Currnent-Mode Circuits Based on CNTFET Technology - Moradi, Mona (International Journal of Computer (IJC), 2016)
Computational operations are considered as a time-consuming and important operation in ALU. These circuits play major role in computational operation in processing unit. This paper presents new computational Ternary Current Mode Circuits including comparator, multiplexer, decoder, and exclusive OR by means of Carbon NanoTube Field Effect Transistors. The new designs rely on three major parts: 1) the input currents which are converted to voltage; 2) threshold detectors; and 3) the output current flow paths to generate the outputs. The designs have been simulated based on 32nm CNFTET using Synopsys Hspice simulator.